Anti-Intellectualism in Catholic Colleges - Greeley, Andrew (The American catholic sociological review, 1962)
The frequently heard charge of anti-intellectualism against American Catholic colleges is examined against data taken in a June 1961 representative sample of college graduates. On most indicators of "intellectualism" the graduates of Catholic colleges scored no lower than the national average. There seemed to be no disinclination on the part of these graduates to enter scholarly careers. Some evidence is present that this is the result of a major social change and that the faculties of Catholic colleges are putting pressure on their gifted students to consider academic careers.